PENGARUH KUALITAS PELAYANAN DAN KEPERCAYAAN TERHADAP LOYALITAS PELANGGAN DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING (Studi Pelanggan di PT. Indo Samudera Perkasa Semarang) - Wicaksono, Yoga; Santosa, Suryono Budi (Faculty of Economics and Business Diponegoro University, 2015)
This study aimed to analyze the impact of service quality on customer loyalty and trust with customer satisfaction as an intervening variable. This study used a multiple linear regression analysis using SPSS. The population used is the customers who have used the services of PT. Indo Samudera Perkasa representing 100 people. While the sample used as many as 100 people with the sample selection technique is a census study. The results showed that the quality of service and trust affects customer satisfaction and customer satisfaction influence on customer loyalty. In model 1, the quality of service gives the greatest influence to the satisfaction of 0.524. In model 2, the quality of service gives the greatest influence on customer loyalty by 0.340.